A methodology for automated design and implementation of complex analog and digital CMOS integrated circuits applying a genetic algorithm and a CAD tool for multiobjective optimization - Pereira-Arroyo, Roberto (2014)
Tesis (Doctorado en Ciencias Naturales para el Desarrollo) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2014.